Leveraging Interactive Learning by Integrated Assessment Software in EdTech: Enhancing Sustained Learning Outcomes with Mentimeter - Deshmukh, Sujata Pravin Shinde; Kulkarni, Vinay; Malathi, P (Journal of Engineering Education Transformations, 2025)
The advent of Educational Technology (EdTech) has transformed traditional pedagogical approaches, introducing innovative tools that enhance engagement and learning outcomes. This paper explores the application of Mentimeter, an interactive presentation software, in educational settings. By integrating features such as live polls, quizzes and word clouds, Mentimeter fosters a more interactive and participatory learning environment. The study investigates how real time feedback and immediate assessment capabilities enable educators to adjust their teaching strategies dynamically, thus catering to individual student needs and promoting active engagement in learning. Additionally, the paper examines Mentimeter’s role in increasing inclusivity and accessibility, allowing anonymous participation and accommodating both in person and remote learners. The analysis includes data-drive insights derived from student responses, highlighting the tool’s effectiveness in improving student engagement, collaboration and overall learning outcomes. This research contributes to the broader understanding of how interactive presentation software can be utilized within the EdTech framework to enhance educational experiences and support data driven instructional practices. The findings underscore the potential of interactive presentation tools in digitizing modern education, making a compelling case for their widespread adoption in classrooms and beyond.